Factor VIII and von Willebrand Factor - Vlot, André J.; Koppelman, Stefan J.; Bouma, Bonno N.; Sixma, Jan J. (Thrombosis and Haemostasis, 1998)
Factor VIII and von Willebrand factor are plasma glycoproteins whose deficiency or structural defects cause hemophilia A and von Willebrand disease, respectively (1). These diseases are the most common inherited bleeding disorders of man. Factor VIII and vWF are synthesized by different cell types and circulate in plasma as a tightly bound complex. Factor VIII is synthesized in the liver (2), and functions as a cofactor for activated factor IX in the intrinsic activation of factor X on a membrane surface (3). vWF is synthesized in endothelial cells (4, 5) and megakaryocytes (6). vWF has a dual role in hemostasis: it promotes platelet adhesion to subendothelium after vessel injury (7, 8) and it acts as a carrier protein of factor VIII (1).The distinction between factor VIII and vWF was unclear for many years, because severe Von Willebrand disease is associated with factor VIII deficiency and because early preparations of factor VIII concentrates contained vWF and were therefore effective in correcting the platelet adhesion defects in patients with von Willebrand disease (9). Since factor VIII and vWF form a tightly bound non-covalent complex in plasma, both proteins are copurified when isolated from plasma, unless special measures are taken (1). The stoichiometry of factor VIII and vWF in plasma is approximately 1:50 and factor VIII and monomeric vWF have similar molecular weights of approximately 240 kDa. Therefore, vWF represents 98% of the molecular mass of the factor VIII-vWF complex (10) and almost all the antibodies raised against the complex react to vWF. In the 1980’s, factor VIII and vWF have each been purified to homogeneity and the genes for these proteins have been cloned. This set the stage for studies with purified proteins which have elucidated structure-function relationships for both proteins. Also, the interaction between both proteins could be studied using proteolytic fragments, small peptides, and monoclonal antibodies. In the last few years, the construction of recombinant mutants and fragments of both factor VIII (11-13) and vWF (14-16) has proven to be a powerful tool in the elucidation of the structure and function of both proteins.Binding of factor VIII to vWF is essential for the survival of factor VIII in vivo (17, 18). The underlying mechanism is probably that factor VIII bound to vWF is protected from phospholipid dependent proteolysis by activated protein C and factor Xa (19, 20). The binding site for factor VIII has been located at the amino terminus of vWF (21, 22). A tryptic fragment containing this binding site was not sufficient to protect factor VIII against activated protein C-mediated degradation according to some groups (23, 24). In contrast, a recent study using comparable vWF fragments showed protection of factor VIII equivalent to mature vWF (16).In 1989, a new variant of von Willebrand disease was discerned (type Normandy or 2N), distinct from the more than 20 subtypes known, characterized by a mutant vWF that is structurally and functionally normal, except that it does not bind to and stabilize factor VIII (25, 26). Since then, several mutations in the factor VIII binding site on vWF have been found (27). A number of reports have shown that factor VIII binds vWF via a high affinity binding site on its light chain (28-30). Two recent studies suggest that this binding site consists of two separate binding sites (31, 32).This review summarizes current knowledge on the interaction between factor VIII and vWF. Emphasis will be laid on the biological importance of, and the domains involved in binding, and on the stoichiometry and kinetics of complex formation.